The Error of Global Ionospheric Map‐TEC During Equatorial Plasma Bubble Event in the High Solar Activity Year - Long Tang; Fenkai Zhang; Wu Chen (Space Weather)
Abstract In this study, the error of total electron content (TEC) derived from the global ionospheric map (GIM) (GIM‐TEC) during equatorial plasma bubble (EPB) event is investigated for the first time. The frequently‐used assessment parameter of ionospheric TEC model, namely difference of Slant TEC (difference of slant total electron content (dSTEC)) is checked and employed based on eight global navigation satellite system (GNSS) stations distributed around the geomagnetic equator during the high solar activity year of 2014. The international GNSS service final GIM products are exemplified. The results present several interesting findings: (a) The observed dSTEC series is biased when an EPB is observed at the highest satellite elevation, leading to a fake bias in GIM‐TEC; (b) When an EPB occurred, the error of GIM‐TEC can increases or decreases and its variation sign is unrelated to the magnitude of EPB; (c) The average of the EPB‐induced GIM‐TEC errors is mainly at −5 to 5 TECU with 76% (24%) of positive (negative) values, and the maximum (minimum) is close to 10 TECU (−10 TECU); (d) The structure of EPB is unable to be captured by the GIM‐TEC series.